Influence of Input Parameters on the Coefficient of Friction during Incremental Sheet Forming of Grade 5 Titanium Alloy Sheets - Szpunar, Marcin; Szawara, Paulina; Myśliwiec, Piotr; Ostrowski, Robert (Advances in Mechanical and Materials Engineering, 2023)
This research paper focuses on investigating the influence of input parameters on the coefficient of friction (COF) during incremental sheet forming (ISF) of grade 5 titanium sheets. Titanium alloys are widely used in various industries due to their corrosion resistance and strength to weight ratio. ISF is a flexible and cost effective process for producing complex shapes. The aim of this study was to gain insight into the frictional conditions during ISF that affect formability, surface quality, and overall process performance. The experiments were carried out using a combination of MoS2 lubrication and friction stir rotation-assisted heating. COF was measured using a high precision piezoelectric dynamometer, taking into account axial and horizontal forces. A split-plot design was used and 25 runs were performed to obtain the COF for each run. The results of the study provide valuable information on the relationship between input parameters and COF, contributing to the understanding of the frictional conditions in the ISF.